STUDYING THE ROLE AND MECHANISM OF MICROORGANISMS IN THE PRODUCTION OF MICROBIOLOGICAL FERTILIZERS - Voqqosov, Zuxriddin (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
Abstract. In this article, we will discuss the identification and mechanism of the application of microorganisms to fertilizers in soil processing. This will help to provide microbiological fertilizer research processes and provide new prospects for the development of new agents, especially microorganisms in the production of microbiological fertilizers in economic agriculture. The research conducted by us was carried out on 3 types of local raw materials: Cattle manure, Poultry manure, Freshwater sludge in the ratio of 100: (35): (50) and selected microorganisms Bacillus sp, Rhizobium sp, Azotobacter sp. in the ratio of 1; 1; 2 for 35 days. As a result, the amount of GK, FK and OM in the fertilizer mixture was 2.08-4.4%, 4.10-4.53% and 30.01-41.8%, respectively, after 35 days. The change in the chemical composition during the composting process was studied.